2019
DOI: 10.1101/732321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of a priori-identified addiction and smoking gene sets in smoking behaviors

Abstract: Introduction:Smoking is a leading cause of death, and genetic variation contributes to smoking behaviors. Identifying genes and sets of genes that contribute to risk for addiction is necessary to prioritize targets for functional characterization and for personalized medicine. Methods:We performed a gene set-based association and heritable enrichment study of two addiction-related gene sets, those on the Smokescreen Genotyping Array and the nicotinic acetylcholine receptors, using the largest available GWAS su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…13 Pre-clinical models have identified several differentially regulated pharmacological targets for a personalized approach to treating nicotine dependence. [14][15][16] However, people who smoke have unique profiles that are influenced by their habits, personality, lifestyle, and sociocultural exposure in addition to their genetics, metabolism, and physical and mental health status. 2 Expanding the scope of treatment to include psychological, behavioral, neurobiological, and social contributions to the development and maintenance of TUD will improve treatment precision and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…13 Pre-clinical models have identified several differentially regulated pharmacological targets for a personalized approach to treating nicotine dependence. [14][15][16] However, people who smoke have unique profiles that are influenced by their habits, personality, lifestyle, and sociocultural exposure in addition to their genetics, metabolism, and physical and mental health status. 2 Expanding the scope of treatment to include psychological, behavioral, neurobiological, and social contributions to the development and maintenance of TUD will improve treatment precision and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Unique challenges exist for cross-species data integration, including homology of genes and the substantial differences between human and model organism phenotypes. There is an urgent need to understand whether and under what conditions genes identified in model organism genomic studies of addiction are also implicated in human GWASs of related traits 14 . Few studies have systematically examined the overlap of genes identified in rodent paradigms that model aspects of addiction [15][16][17][18] with those identified in humans.…”
Section: Introductionmentioning
confidence: 99%